2011
DOI: 10.1152/ajpregu.00301.2011
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent mediators of HPA axis activation following live Escherichia coli

Abstract: Zimomra ZR, Porterfield VM, Camp RM, Johnson JD. Time-dependent mediators of HPA axis activation following live Escherichia coli . Am J Physiol Regul Integr Comp Physiol 301: R1648-R1657, 2011. First published September 14, 2011 doi:10.1152/ajpregu.00301.2011.-The hypothalamus-pituitary-adrenal (HPA) axis is activated during an immune challenge to liberate energy and modulate immune responses via feedback and regulatory mechanisms. Inflammatory cytokines and prostaglandins are known contributors to HPA activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 63 publications
(74 reference statements)
1
17
0
Order By: Relevance
“…Prostaglandins may stimulate corticosterone release through an ACTH-independent mechanism. Studies have further shown that the level of corticosterone is also associated with IL-6 [52,53]. In our study, the corticosterone level decreased after treatment with the antibiotics, while L. paracasei N1115 was shown to induce this abnormal change.…”
Section: Increasing Attention Is Being Focused On Exploring the Benefsupporting
confidence: 60%
“…Prostaglandins may stimulate corticosterone release through an ACTH-independent mechanism. Studies have further shown that the level of corticosterone is also associated with IL-6 [52,53]. In our study, the corticosterone level decreased after treatment with the antibiotics, while L. paracasei N1115 was shown to induce this abnormal change.…”
Section: Increasing Attention Is Being Focused On Exploring the Benefsupporting
confidence: 60%
“…There is no consistent relationship between cortisol levels and the anthro-pometric and metabolic parameters in obesity (Abraham et al, 2013); however, intestinal mast cells can be activated by high fat intake thereby modulating the intestinal release of mediators such as PGs, leukotrienes, and cytokines (Ji et al, 2011; Abraham et al, 2013). PGs and inflammatory cytokines can interfere with HPA activation to promote direct or indirect regulation of gut permeability (Keita and Soderholm, 2010; Vicario et al, 2010; Zimomra et al, 2011). In addition, although not explored in this study, fat consumption and stress are likely to promote changes in micro-biota that could trigger a “leaky gut” inflammatory syndrome, which would be expected to disrupt the gut-brain axis and impact behavior (Kelly et al, 2015; Bailey, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Signals from the gut are well known to activate the HPA axis: both infection by pathogenic bacteria and stimulation of the vagus nerve elicit corticosterone release (Hosoi et al, 2000; Zimomra et al, 2011). Altered microbiota-brain-gut signalling is thought to play a role in the pathogenesis of GI disorders; patients with IBS have both an altered gut microbiota composition and irregular HPA axis activity (Jeffery et al, 2012; Kennedy et al, 2014a, 2014c).…”
Section: Introductionmentioning
confidence: 99%